Safety assessment of symptomatic intracranial atherosclerotic stenosis: a comparison between sole balloon angioplasty and medical treatment - Cao, Wen-feng; Wen, An; Cao, Xian-min; Wu, Ling-feng; Zhou, Yong-liang; Xiang, Zheng-bing; Rao, Wei; Chu, Quan-hong; Hong, Wang-Wang; Liu, Shi-min (Frontiers in Neurology, 2025)
BackgroundPatients with symptomatic intracranial arterial stenosis (sICAS) are at risk of perioperative complications associated with stent placement and medication recurrence. Simple balloon angioplasty (SBA), a less invasive and safer alternative to stent placement, is an effective alternative treatment for sICAS.MethodsWe conducted a retrospective analysis on patients with sICAS treated at the Jiangxi Provincial People’s Hospital between January 2020 and December 2023. Patients with severe stenosis (70–99%) were divided into the medical management (MM) and SBA groups. Demographics, medical histories, National Institutes of Health Stroke Scale (NIHSS) scores, vessel stenosis, postoperative residual stenosis, and 30-day outcomes were also assessed.ResultsThis study enrolled 176 patients, including 95 (66 males, mean age 57.4 ± 1.07 years) and 81 (55 males, mean age 61.1 ± 0.94 years) in the MM and SBA groups, respectively. Patients in the SBA group were significantly older than those in the MM group (p < 0.05). No significant differences were observed in sex, comorbidities (hypertension, diabetes, hyperlipidemia, smoking/alcohol use, and prior stroke), or baseline NIHSS scores (all p > 0.05). Pre-treatment stenosis rates were similar between groups: 80.90 ± 0.85% vs. 79.60 ± 1.01% (p > 0.05). One patient in the SBA group failed due to vessel tortuosity, while the remaining 80 procedures were successful. Of these, 15 patients (18.5%) required rescue stenting—11 because of elastic recoil and 4 because of flow-limiting dissection. The immediate residual stenosis rate was 24.68 ± 1.41%. Within 30 days, endpoint events occurred in four patients (4.2%) in the medical group (progressive infarction) and seven patients (8.6%) in the angioplasty group, including intracerebral and subarachnoid hemorrhage (n = 2), perforator infarction (n = 3), infarct progression (n = 1), and cortical infarction (n = 1). No deaths occurred in either group. The difference in the event rates was not statistically significant (p > 0.05). Subgroup analysis revealed that arterial dissection was significantly associated with postoperative endpoint events (p < 0.05), while occurrence was correlated with lesion length (p < 0.05), but not with the selected balloon size (p > 0.05). There was no significant difference in endpoint events between submaximal (< 90% of normal vessel diameter) and aggressive (> 90% of normal vessel diameter) angioplasties (p > 0.05).ConclusionOverall, this study suggests that SBA does not significantly increase the 30-day risk of stroke or death in patients with sICAS compared with medical therapy. Both submaximal and aggressive angioplasty are safe. Further research is warranted to refine patient selection, optimize balloon size, and develop strategies to minimize the need for rescue stenting and reduce the risk of arterial dissection.